Kynurenine pathway in Coronavirus disease (COVID‐19): Potential role in prognosis. Issue 3 (29th January 2022) - Cihan, Murat; Doğan, Özlem; Ceran Serdar, Ceyhan; Altunçekiç Yıldırım, Arzu; Kurt, Celali; Serdar, Muhittin A.
Abstract: Background: It is known that inflammatory responses play an important role in the pathophysiology of COVID‐19. Aims: In this study, we aimed to examine the role of kynurenine (KYN) metabolism on the severity of COVID‐19 disease AQ5. Materials & Methods: Seventy COVID‐19 patients of varying severity and 30 controls were included in the study. In addition to the classical laboratory parameters, KYN, tryptophan (TRP), kynurenic acid (KYNA), 3 hydroxykynurenine (3OHKYN), quinolinic acid (QA), and picolinic acid (PA) were measured with mass spectrometry. Results: TRP, KYN, KYN:TRP ratio, KYNA, 3OHKYN, PA, and QA results were found to be significantly different in COVID‐19 patients ( p  < 0.001 for all). The KYN:TRP ratio and PA of severe COVID‐19 patients was statistically higher than that of mild‐moderate COVID‐19 patients ( p  < 0.001 for all). When results were examined, statistically significant correlations with KYN:TRP ratio, IL‐6, ferritin, and procalcitonin were only found in COVID‐19 patients. ROC analysis indicated that highest AUC values were obtained by KYN:TRP ratio and PA (0.751 vs 0.742). In determining the severity of COVID‐19 disease, the odd ratios (and confidence intervals) of KYN:TRP ratio and PA levels that were adjusted according to age, gender, and comorbidity were determined to be 1.44 (1.1–1.87, p  = 0.008) and 1.06 (1.02–1.11, p  = 0.006), respectively. Discussion & Conclusion: According to the results of this study, KYN metabolites play a role in the pathophysiology of COVID‐19, especially KYN:TRP ratio and PA could be markers for identification of severe COVID‐19 cases. Abstract : It has been shown that the kynurenine (KYN) pathway plays an important role in the regulation of the immune system. KYN pathway products were found to be significantly different in COVID‐19 patients. KYN:TRP ratio and picolinic acid (PA) of severe COVID‐19 patients was statistically higher than of mild‐moderate COVID‐19 patients. ROC analysis indicated that highest AUC values were obtained by KYN:TRP ratio and PA (0.751 vs 0.742). In determining the severity of COVID‐19 disease, the odd ratios (and confidence intervals) of KYN:TRP ratio and PA levels that were adjusted according to age, gender, and comorbidity were determined to be 1.44 (1.1–1.87, p  = 0.008) and 1.06 (1.02–1.11, p  = 0.006), respectively. According to the results of this study, KYN metabolites play a role in the pathophysiology of COVID‐19, especially KYN:TRP ratio and PA could be markers for identification of severe COVID‐19 cases.